Designing Augmented Reality-Based Multimedia Using Experimental Methods to Improve Students' Cognitive in Basic Network Subject - Sumitra, Desfasa Ilham; Setiawan, Wawan; Rasim, Rasim (Jurnal Guru Komputer, 2023)
This study aims to determine the cognitive increase that occurs in students, after being given treatment in the form of learning using-based learning multimedia Augmented Reality with VAK (learning models Visualization, Auditory, Kinesthetic) in Basic Network subjects. The subjects of this study were students of class X (ten) at one of the vocational schools in the district, West Bandung. The background of this research is the learning model used previously in the teaching process is less effective, the multimedia used by the teacher is too monotonous and the lack of understanding and student activity in the learning process. The research method used in this research is quantitative and the teaching method used is experimental. While the application development method used is SHM (Comprehensive Life Cycle) and the results obtained from this study are: 1) Interactive multimedia is considered good and suitable for use. The presentation score was 83.99% which was interpreted as "Very good" by media experts and teachers, 2) The interactive multimedia can also improve students' cognitive and obtained an average gain value of 0.67 with the "Medium" effectiveness criteria. Meanwhile, the students' response to the based on Augmented Reality-based multimedia obtained an average score of 81.19% and is included in the "Good" category.